2019
DOI: 10.3390/su11113169
|View full text |Cite
|
Sign up to set email alerts
|

Injury Severity of Bus–Pedestrian Crashes in South Korea Considering the Effects of Regional and Company Factors

Abstract: Bus-pedestrian crashes typically result in more severe injuries and deaths than any other type of bus crash. Thus, it is important to screen and improve the risk factors that affect bus-pedestrian crashes. However, bus-pedestrian crashes that are affected by a company's and regional characteristics have a cross-classified hierarchical structure, which is difficult to address properly using a single-level model or even a two-level multi-level model. In this study, we used a cross-classified, multi-level model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The findings of this study are in line with those of Onieva-García et al [63], Toran Pour et al [64], Park and Ko [65], Li and Fan [44], and Kim et al [66], who confirmed the significant roles of age and gender in pedestrian-related crashes and deaths. Several studies also confirmed the effects of bus involvement on the risks of injury and death of pedestrians (e.g., [67][68][69]), which indicates the significant role of crash attributes in the prediction of PDRC. Overall, when personal characteristics and crash features are factored in, this model appears to be successful and accurate.…”
Section: Variable Significancementioning
confidence: 75%
“…The findings of this study are in line with those of Onieva-García et al [63], Toran Pour et al [64], Park and Ko [65], Li and Fan [44], and Kim et al [66], who confirmed the significant roles of age and gender in pedestrian-related crashes and deaths. Several studies also confirmed the effects of bus involvement on the risks of injury and death of pedestrians (e.g., [67][68][69]), which indicates the significant role of crash attributes in the prediction of PDRC. Overall, when personal characteristics and crash features are factored in, this model appears to be successful and accurate.…”
Section: Variable Significancementioning
confidence: 75%
“…In addition, factors such as drinking status [38], driving experience [32], time [39], road structure [40], vehicle age [41], and visibility [42] have been considered as individual characteristics of pedestrian crashes.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Driver’s residence, working hours, income satisfaction, and negative passenger behavior were identified as major contributing factors based on an ordered probit model ( 20 ). Park et al analyzed factors influencing bus-pedestrian traffic accidents ( 21 ). The identified regional-level factors included the proportion of elderly people, transport infrastructure budget, and the number of medical doctors.…”
mentioning
confidence: 99%
“…The identified regional-level factors included the proportion of elderly people, transport infrastructure budget, and the number of medical doctors. Also, they suggested safety countermeasures based on the derived factors ( 21 ).…”
mentioning
confidence: 99%